2016
DOI: 10.1039/c6ay02555b
|View full text |Cite
|
Sign up to set email alerts
|

A label-free electrochemical immunosensor for the detection of cancer biomarker α-fetoprotein (AFP) based on hydroxyapatite induced redox current

Abstract: An electrochemical immunosensor for label-free detection of cancer biomarker α-fetoprotein (AFP) was developed based on hydroxyapatite (HAP) nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Table 1 Assay results of AFP in serum samples Table 2 shows the analytical performance of other methods for AFP detection. This new one-step detection method has a low (Limit of Detection) LOD and wide range of detection similar to or better than previously reported ways [36][37][38][39][40][41] . However, the system provides cost-effective testing with a simple measuring process.…”
Section: Detection Of Afp In Human Serum Samplessupporting
confidence: 77%
“…Table 1 Assay results of AFP in serum samples Table 2 shows the analytical performance of other methods for AFP detection. This new one-step detection method has a low (Limit of Detection) LOD and wide range of detection similar to or better than previously reported ways [36][37][38][39][40][41] . However, the system provides cost-effective testing with a simple measuring process.…”
Section: Detection Of Afp In Human Serum Samplessupporting
confidence: 77%
“…Finally, the practical applicability of the aptasensor was verified by analyzing human serum samples using the standard addition method. 112 Carbon nanotubes (CNTs).-Because of their special qualities, CNTs (Fig. 6) can be used to create highly sensitive and stable biosensors for detecting AFP.…”
Section: Experimental Issues In Afp Detectionmentioning
confidence: 99%
“…Vennila et al employed an environmentally friendly method for synthesizing silver-doped cerium oxide nanoparticles for electrochemical glucose detection [21]. They demonstrated that the current amplifies and produces a measurable amount of electrocatalytic current due to the generation of H 2 O 2 by the glucose oxidase enzyme.…”
Section: Introductionmentioning
confidence: 99%